2017
DOI: 10.1111/pre.12191
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of chlorophylls and carotenoids from freshwater algae using different extraction methods

Abstract: SUMMARY Usually marine algae are an excellent source of pigments for different commercial sectors. Freshwater macroalgae can be exploited as a good source of biologically active compounds provided an appropriate extraction method is developed. The efficiency of four methods, like microwave‐assisted (MAE), ultrasound‐assisted extraction (UAE), supercritical fluid extraction (SFE) with ethanol as a co‐solvent, as well as conventional Soxhlet extraction were studied in the same conditions (time, solvent and tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 29 publications
1
26
0
1
Order By: Relevance
“…In other studies, MAE and UAE methodologies were shown to be the more efficient techniques for the chlorophyll and carotenoid isolation from freshwater green algae: C. glomerata , C. rivularis and U. flexuosa compared to the Soxhlet extraction and solid phase extraction [ 191 ].…”
Section: Novel Liquid–liquid and Solid–liquid Extraction Technologmentioning
confidence: 99%
“…In other studies, MAE and UAE methodologies were shown to be the more efficient techniques for the chlorophyll and carotenoid isolation from freshwater green algae: C. glomerata , C. rivularis and U. flexuosa compared to the Soxhlet extraction and solid phase extraction [ 191 ].…”
Section: Novel Liquid–liquid and Solid–liquid Extraction Technologmentioning
confidence: 99%
“…Each extract was dissolved with acetone p.a at 100 ppm and measured at a wavelength of 645 nm, 662 nm and 470 nm [26]. Most carotenoids absorb lights in the region between 400 and 500 nm, while chlorophylls absorb light at 645 and 662 nm at room temperature [27].…”
Section: Assessment Of Chlorophyll a And Carotenoids Compoundsmentioning
confidence: 99%
“…Using sonication in water (and subsequent ammonium sulphate-induced protein precipitation) provided the greatest protein yields, but the protein and fatty acids content was higher with the alkaline protein solubilization [87]. An optimized ultrasound-assisted extraction of crude Ulva sulphated polysaccharides showed radical scavenging, reducing power and a macrophage-stimulating capacity [100].…”
Section: Emerging Technologiesmentioning
confidence: 99%